From Survival to Sustainability: Reengineering Healthcare Workforce Resilience Through Cognitive Reserve - De Guzman, Jomar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the role of cognitive reserve in strengthening healthcare workforce resilience among 137 healthcare workers from different medical facilities in the Philippines. Anchored on cognitive reserve theory and the Job Demands–Resources theory, the study used a quantitative research design to assess patterns among cognitive reserve, workforce resilience, burnout-related strain, organizational support, professional development, and sustainability orientation. The specific research instrument and sampling procedure were not identified in the provided text. Findings showed that respondents had high cognitive reserve (M = 4.08, SD = 0.54) and high workforce resilience (M = 4.02, SD = 0.57), while burnout-related strain was moderate (M = 3.21, SD = 0.73) and organizational support was also moderate (M = 3.48, SD = 0.68). Cognitive reserve had a strong positive relationship with workforce resilience (r = .68, p < .001) and a moderate negative relationship with burnout-related strain (r = -.46, p < .001). Organizational support was also positively related to resilience (r = .52, p < .001). Regression results showed that cognitive reserve, organizational support, professional development orientation, and burnout-related strain significantly predicted workforce resilience, explaining 56.0% of its variance. The study concludes that healthcare workforce resilience is shaped by both personal cognitive resources and institutional support systems. It recommends strengthening continuing education, reflective learning, adaptive problem-solving, psychological safety, supportive leadership, teamwork, and burnout reduction initiatives. The study aligns with SDG 3, SDG 4, SDG 8, SDG 9, and SDG 17 by supporting public health, quality education, decent work, institutional innovation, and collaborative workforce development. Its sustainability impact centers on strengthening healthcare institutions, improving workforce retention, and supporting safer and more resilient health service delivery.